Synthesis and anti-oomycete activity of novel quinazolin- and benzothiazol-6-yloxyacetamides: Potent aza-analogs and five-ring analogs of quinoline fungicides. Issue 3 (1st February 2016) - Beaudegnies, Renaud; Quaranta, Laura; Murphy Kessabi, Fiona; Lamberth, Clemens; Knauf-Beiter, Gertrud; Fraser, Torquil
Graphical abstract: Abstract: Novel quinazolin- and benzothiazol-6-yloxyacetamides show excellent in vivo activity against the three economically most important Oomycete pathogens Phytophthora infestans, Plasmopara viticola and Pythium ultimum . They are polar analogs of known quinolin-6-yloxyacetamides, which are not active against the soil-borne damping-off disease caused by Pythium ultimum . The Bogert quinazoline synthesis, an almost forgotten heterocyclization technique, proved to be highly useful for the concise construction of required quinazolin-6-ol building blocks.